Bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst and preparation method and application thereof
By designing a composite photocatalyst of bismuth-rich bromine oxide, polyaniline and graphene oxide, the problem of failure to combine bismuth-bromoxib, polyaniline and graphene in the prior art is solved, and efficient visible photocatalytic performance is achieved, simplifying the The preparation process was carried out.
Patent Information
- Application Number
- CN202010944977.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-09-10
AI Technical Summary
The prior art has not yet combined bismuth bromine oxide, polyaniline and graphene simultaneously to prepare a composite photocatalyst, resulting in the failure of the photocatalytic performance to be fully exerted.
A composite photocatalyst of bismuth-rich bromine oxide, polyaniline and graphene oxide was designed, through specific component ratios and preparation methods, including adding bismuth-rich bromine oxide to polyaniline and graphene oxide solutions, and after ultrasonic treatment Stir, filter, wash and dry to prepare a highly efficient visible photocatalyst.
The light absorption area is extended through the introduction of polyaniline, and the long-wave light is effectively utilized, which improves the visible photocatalytic performance of the composite photocatalyst. The preparation process is simple and the catalytic performance is greatly improved.
Smart Images

Figure CN114160197B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalytic water decomposition to produce hydrogen, and in particular to a bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst, and a preparation method and application thereof. Background Art
[0002] Energy issues have always been an important issue of concern to people. With the increasing consumption of the earth's energy reserves and the increasing environmental problems caused by over-exploitation, people have gradually focused on how to use natural clean energy to meet human needs. Using solar energy to decompose water to obtain H2 and O2 not only meets people's demand for energy but also does not cause environmental problems. This method not only produces a carbon-free fuel, but also achieves the sustainable development of the environmental system.
[0003] Bismuth oxybromide has great potential as a photocatalyst. By changing the preparation method and conditions, the size, morphology and crystal structure of bismuth oxybromide photocatalyst can be regulated, thereby improving its photocatalytic activity. As a ternary semiconductor material, bismuth oxybromide has highly anisotropic layered structure, high chemical stability and suitable bandgap width and other physical and chemical properties, showing excellent electrical, magnetic and optical properties. In recent years, bismuth oxyhalide has become a new direction of photocatalyst due to its good physical and chemical properties and visible light response.
[0004] Polyaniline (PANI) is an important conductive polymer with a π-π conjugated electronic structure. It is also regarded as an organic narrow bandgap (2.8eV) semiconductor, which can effectively conduct photogenerated electrons, improve the separation efficiency of photogenerated electrons and holes in the material, and improve the photocatalytic activity of the material. PANI has a high absorption coefficient in the visible light region and can directly utilize sunlight.
[0005] Graphene is a monolayer structure of two-dimensional carbon atoms. It has excellent electrical properties, high light transmittance, flexible structure, high specific surface area and thermal conductivity. It has potential applications in composite materials, batteries, solar cells and photocatalysis. Among them, its good conductivity and large specific surface area make graphene a photocatalyst carrier. If graphene is introduced into semiconductor materials and their synergistic effects are brought into play, the photocatalytic performance of the materials will be effectively improved.
[0006] However, up to now, there has been no composite photocatalyst prepared by combining the above-mentioned bismuth oxyhalide, polyaniline and graphene at the same time, so there is an urgent need to design a composite photocatalyst with better photocatalytic performance. Summary of the invention
[0007] In order to improve the visible light catalytic performance of the composite photocatalyst, the object of the present invention is to provide a bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst, which has efficient visible light catalytic hydrogen production performance.
[0008] Another object of the present invention is to provide a method for preparing the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst.
[0009] Another object of the present invention is to provide an application of the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst in the production of hydrogen.
[0010] To achieve the above objectives, on the one hand, the present invention provides a bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst, comprising the following components in parts by weight: 80-98 parts of bismuth-rich oxybromide, 1-10 parts of polyaniline, and 1-5 parts of graphene oxide.
[0011] The bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst prepared by the present invention has efficient visible light catalytic performance, which may be attributed to the fact that the introduction of polyaniline is conducive to extending the light absorption region and more effectively utilizing long-wave light, while the change in the element ratio leads to the improvement of the photocatalytic performance.
[0012] According to some specific embodiments of the present invention, the bismuth-rich oxybromide comprises Bi 24 O 31 Br 10 .
[0013] According to some specific embodiments of the present invention, the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst is prepared by a method comprising the following steps: adding bismuth-rich oxybromide to a polyaniline and graphene oxide solution to synthesize the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst.
[0014] According to some specific embodiments of the present invention, the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst is prepared by a method comprising the following steps: adding the bismuth-rich oxybromide to a polyaniline and graphene oxide solution, ultrasonically treating, stirring and filtering, washing the precipitate, and drying to obtain the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst.
[0015] According to some specific embodiments of the present invention, the ultrasonic treatment time is 20-50 min.
[0016] According to some specific embodiments of the present invention, the stirring time is 20-30 hours.
[0017] According to some specific embodiments of the present invention, the precipitate is washed 3-5 times with deionized water.
[0018] According to some specific embodiments of the present invention, the drying condition is drying at 50-80° C. for 20-24 hours.
[0019] According to some specific embodiments of the present invention, the bismuth-rich oxybromide is generated by calcining bismuth oxybromide.
[0020] According to some specific embodiments of the present invention, the bismuth-rich oxybromide is prepared by a method comprising the following steps: (1) dissolving mannitol in deionized water, stirring, and then further adding polyvinyl pyrrolidone and bismuth nitrate to obtain a mixed solution, and then adding potassium bromide solution dropwise to the mixed solution after stirring to form a white precipitate, and then stirring the mixed solution for a period of time, reacting the mixed solution at a specific temperature, cooling to room temperature, and washing and drying the precipitate obtained by centrifuging the mixed solution to obtain a white bismuth oxybromide product; (2) calcining the bismuth oxybromide product to obtain a bismuth-rich oxybromide product.
[0021] According to some specific embodiments of the present invention, in the above step (1), after adding polyvinyl pyrrolidone and bismuth nitrate to obtain a mixed solution, a magnetic stirring rotor is added to stir the mixture for 30-50 minutes.
[0022] According to some specific embodiments of the present invention, in the above step (1), after the white precipitate is formed, the mixture is stirred for 20-30 minutes and then transferred to a reaction kettle with a polytetrafluoroethylene liner and reacted at 140° C.-180° C. for 3 h-5 h.
[0023] According to some specific embodiments of the present invention, in the above step (1), the precipitate obtained by centrifuging the mixed solution is washed with deionized water and ethanol for 3-5 times respectively, and then dried at 60-90° C. for 5-8 h to obtain a white bismuth oxybromide product.
[0024] According to some specific embodiments of the present invention, the polyaniline is prepared by a method comprising the following steps: dissolving aniline and hexadecyltrimethylammonium bromide in deionized water, then dropping hydrochloric acid first and then dropping ammonium persulfate, stirring the reaction and filtering to obtain a precipitate, and then washing and drying the precipitate to obtain polyaniline.
[0025] According to some specific embodiments of the present invention, the rate of adding the ammonium persulfate is 3-5 seconds / drop, the reaction temperature to be maintained during stirring is 0-5°C, and the stirring reaction time is 20-24 hours.
[0026] According to some specific embodiments of the present invention, the precipitate is washed three times with deionized water and three times with acetone, and vacuum dried at 60-70° C. for 15-18 hours to obtain conductive polyaniline.
[0027] According to some specific embodiments of the present invention, the polyaniline and graphene oxide solution is prepared by a method comprising the following steps: dispersing polyaniline and graphene oxide in a mixed solution of deionized water, isopropanol and tetrahydrofuran and mixing them uniformly to obtain the polyaniline and graphene oxide solution.
[0028] On the other hand, the present invention also provides a method for preparing the above-mentioned bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst, comprising the following steps: adding bismuth-rich oxybromide into a polyaniline and graphene oxide solution to synthesize the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst.
[0029] According to some specific embodiments of the present invention, the preparation method comprises the following steps: (1) Preparation of polyaniline and graphene oxide solution: dissolving aniline and hexadecyltrimethylammonium bromide in deionized water, then dropping hydrochloric acid first and then dropping ammonium persulfate, stirring the reaction, filtering to obtain a precipitate, washing and drying the precipitate to obtain polyaniline, dispersing polyaniline and graphene oxide in a mixed solution of deionized water, isopropanol and tetrahydrofuran and mixing them evenly to obtain a polyaniline and graphene oxide solution; (2) Preparation of bismuth oxybromide: dissolving mannitol in deionized water, stirring, then further adding polyvinyl pyrrolidone and bismuth nitrate to obtain a mixed solution, stirring and then dropping potassium bromide solution into the mixed solution to form a white precipitate, stirring for a period of time, reacting the mixed solution at a specific temperature, cooling to room temperature after the reaction is completed, and washing and drying the precipitate obtained by centrifuging the mixed solution to obtain a white bismuth oxybromide product; (3) Preparation of bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst (i.e., Bi 24 O 31 Br 10 Preparation of PANI and GO composite photocatalysts: The prepared white bismuth oxybromide product is calcined to obtain Bi 24 O 31 Br 10 Light yellow solid, then a certain amount of Bi 24 O 31 Br 10 The powder is added to the polyaniline and graphene oxide solution, and then ultrasonically treated, stirred, filtered, washed, precipitated, and dried to obtain Bi 24 O 31 Br 10 , PANI and GO composite photocatalysts.
[0030] According to some specific embodiments of the present invention, in step (1), the molar ratio of aniline to hexadecyltrimethylammonium bromide is 10:1.
[0031] According to some specific embodiments of the present invention, in step (1), the rate of adding the ammonium persulfate is 3-5 seconds per drop, that is, one drop is added at an interval of 3-5 seconds.
[0032] According to some specific embodiments of the present invention, in step (1), the reaction temperature to be maintained during stirring is 0-5°C.
[0033] According to some specific embodiments of the present invention, the preparation method comprises the following steps: (1) preparation of conductive polyaniline and graphene oxide solution: 0.46g aniline and 0.18g hexadecyltrimethylammonium bromide are dissolved in 80ml deionized water, and then 10ml of 0.5mol / L hydrochloric acid is first added dropwise, and then 10ml of 0.5mol / L ammonium persulfate solution is slowly added dropwise at a rate of 3 seconds / drop, the mixed solution is placed on a magnetic stirrer and stirred, and the reaction temperature is maintained at 0-5°C. After reacting for 24h, the polyaniline precipitate is obtained by suction filtration, and the precipitate is washed three times with deionized water and acetone respectively, and vacuum dried at 70°C for 18h to obtain a conductive polyaniline sample; 0.3g polyaniline and 0.12g graphene oxide are dispersed in deionized water, isocyanate and acetone; Mix evenly in a 1L mixed solution of propanol and tetrahydrofuran; (2) Preparation of bismuth oxybromide: Dissolve 0.556g of mannitol in 25ml of deionized water, stir at room temperature for 30min, then weigh 0.4g of polyvinyl pyrrolidone and 0.486g of bismuth nitrate and add them to the above solution, add a rotor magnetic stirrer and stir the mixture for 30min; Dissolve 3.3g of potassium bromide in 5ml of water to prepare a potassium bromide solution, add it dropwise to the above mixed solution to form a white precipitate, stir for another 30min, transfer the mixed solution to a 50ml polytetrafluoroethylene-lined reactor, react at 160℃ for 3h, take out the reactor and cool to room temperature, wash the precipitate formed by centrifugation with deionized water and ethanol three times respectively, and then dry at 70℃ for 6h to obtain a white bismuth oxybromide product. (3) Bi 24 O 31 Br 10 Preparation of PANI and GO composite photocatalyst: The white bismuth oxybromide prepared above was placed in a muffle furnace and calcined at 550 ° C for 3 h to obtain Bi 24 O 31 Br 10 A pale yellow solid was then added with 2.7 g of Bi 24 O 31 Br 10 The powder was added to 100 ml of a mixed solution of deionized water, isopropanol and tetrahydrofuran with a PANI concentration of 0.3 g / L and a graphene oxide concentration of 0.12 g / L, and ultrasonically treated for 30 min. The mixed solution was then stirred for 24 h. The mixed suspension was filtered, the precipitate was washed with deionized water for 3 times, and dried at 60 ° C for 24 h to obtain Bi 24 O31 Br 10 , PANI and GO composite photocatalysts.
[0034] On the other hand, the present invention also provides the use of the above-mentioned bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst in the production of hydrogen.
[0035] According to some specific embodiments of the present invention, the step of producing hydrogen includes: dispersing the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst in a closed reactor filled with methanol aqueous solution, continuously irradiating with a xenon lamp, maintaining a certain temperature and an appropriate stirring speed, adding the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst once at intervals, and finally detecting the hydrogen production by gas chromatograph, preferably detecting the hydrogen production by gas chromatograph TCD.
[0036] According to some specific embodiments of the present invention, a 300W xenon lamp is used for continuous irradiation, the temperature in the closed reactor is 5°C, the stirring speed is maintained at 400rpm, and the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst is added once every 1 hour.
[0037] According to some specific embodiments of the present invention, the step of producing hydrogen comprises: 24 O 31 Br 10 The PANI and GO composite photocatalyst powders were dispersed in 120 mL of methanol aqueous solution, wherein the methanol aqueous solution contained 30 mL of methanol. The top of the reactor was sealed with a rubber ring to make the entire reaction system a closed circulation system (PerfectLight Company Solaredge 700). A 300 W xenon lamp was used for continuous irradiation. During the reaction, the reaction temperature was maintained at 5 ° C. The stirring speed was maintained at 400 rpm. The Bi was added once every 1 h. 24 O 31 Br 10 , PANI and GO composite photocatalysts, and the hydrogen production was detected by gas chromatography TCD.
[0038] Beneficial effects of the present invention:
[0039] The present invention provides a Bi 24 O 31 Br 10 , PANI and GO composite photocatalyst, the introduction of polyaniline in the catalyst is beneficial to prolonging the light absorption area and more effectively utilizing long-wave light. The catalytic performance of the composite photocatalyst prepared by the present invention is greatly improved, and the preparation process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1is a scanning electron microscope image of bismuth oxybromide of Example 1 of the present invention;
[0041] Figure 2 It is a comparison chart of the hydrogen production of Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0042] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0043] Example 1
[0044] This embodiment provides a Bi 24 O 31 Br 10 , PANI and GO composite photocatalyst, and its preparation method is as follows:
[0045] 1.Bi 24 O 31 Br 10 Preparation of PANI and GO composite photocatalyst
[0046] (1) Preparation of conductive polyaniline: 0.46g aniline and 0.18g hexadecyltrimethylammonium bromide were dissolved in 80ml deionized water, and then 10ml of 0.5mol / L hydrochloric acid was added dropwise, and then 10ml of 0.5mol / L ammonium persulfate solution was slowly added dropwise at a rate of 3 seconds / drop. The mixed solution was stirred on a magnetic stirrer, and the reaction temperature was kept at 0-5°C. After reacting for 24h, the polyaniline precipitate was obtained by suction filtration. The precipitate was washed three times with deionized water and acetone respectively, and vacuum dried at 70°C for 18h to obtain a conductive polyaniline sample. 0.3g polyaniline and 0.12g graphene oxide were dispersed in 1L mixed solution of deionized water, isopropanol and tetrahydrofuran and mixed evenly.
[0047] (2) Preparation of bismuth oxybromide: 0.556 g of mannitol was dissolved in 25 ml of deionized water and stirred at room temperature for 30 min. Then, 0.4 g of polyvinyl pyrrolidone and 0.486 g of bismuth nitrate were weighed and added to the above solution. A rotor was added to stir the mixture for 30 min. 3.3 g of potassium bromide was dissolved in 5 ml of water to prepare a potassium bromide solution, which was added dropwise to the above mixed solution to form a white precipitate. After stirring for another 30 min, the mixed solution was transferred to a 50 ml polytetrafluoroethylene-lined reactor and reacted at 160° C. for 3 h. The reactor was taken out and cooled to room temperature. The precipitate formed by centrifugation of the product was washed with deionized water and ethanol three times respectively, and then dried at 70° C. for 6 h to obtain a white bismuth oxybromide product. The scanning electron micrograph of the bismuth oxybromide is shown in FIG. Figure 1 As shown, Figure 1It presents a disordered lamellar structure.
[0048] (3) The white bismuth oxybromide prepared above was placed in a muffle furnace and calcined at 550°C for 3 hours to obtain Bi 24 O 31 Br 10 A pale yellow solid was then added with 2.7 g of Bi 24 O 31 Br 10 The powder was added to a mixed solution of deionized water, isopropanol and tetrahydrofuran with a PANI concentration of 0.3 g / L and a graphene oxide concentration of 0.12 g / L in 1 L, and ultrasonically treated for 30 min. The mixed solution was then stirred for 24 h. The mixed suspension was filtered, the precipitate was washed with deionized water for 3 times, and dried at 60 ° C for 24 h to obtain Bi 24 O 31 Br 10 , PANI and GO composite photocatalysts.
[0049] In the above step (1), the molar ratio of the aniline solution to the hexadecyltrimethylammonium bromide is 10:1;
[0050] In the above step (3), Bi 24 O 31 Br 10 :PANI:GO mass ratio is 90:5:2.
[0051] 2. Hydrogen production test
[0052] Photocatalytic hydrogen production: 24 O 31 Br 10 , PANI and GO composite photocatalyst powders were dispersed in 120 mL of methanol aqueous solution, the methanol content in the methanol aqueous solution was 30 mL, the top of the reactor was sealed with a rubber ring, so that the entire reaction system was a closed circulation system (Perfect Light Company Solaredge 700), and continuously irradiated with a 300 W xenon lamp. During the reaction, the reaction temperature was maintained at 5°C, the stirring speed was maintained at 400 rpm, and samples were taken every 1 hour, and the hydrogen production was detected by gas chromatography TCD.
[0053] Example 2
[0054] This embodiment provides a Bi 24 O 31 Br 10 , PANI and GO composite photocatalyst, and its preparation method is as follows:
[0055] 1.Bi 24 O 31 Br10 Preparation of PANI and GO composite photocatalyst
[0056] (1) Preparation of conductive polyaniline: 0.46g aniline and 0.18g hexadecyltrimethylammonium bromide were dissolved in 80ml deionized water, and then 10ml 0.5mol / L hydrochloric acid was added dropwise, and then 10ml 1mol / L ammonium persulfate solution was slowly added dropwise at a rate of 3 seconds / drop. The mixed solution was stirred on a magnetic stirrer, and the reaction temperature was kept at 0-5°C. After reacting for 24h, the polyaniline precipitate was obtained by suction filtration. The precipitate was washed three times with deionized water and acetone respectively, and vacuum dried at 70°C for 18h to obtain a conductive polyaniline sample. 0.15g polyaniline and 0.04g graphene oxide were dispersed in a 1L mixed solution of deionized water, isopropanol and tetrahydrofuran and mixed evenly.
[0057] (2) Preparation of bismuth oxybromide: 0.556 g of mannitol was dissolved in 25 ml of deionized water and stirred at room temperature for 30 min. Then, 0.4 g of polyvinyl pyrrolidone and 0.486 g of bismuth nitrate were weighed and added to the above solution. A rotor was added to stir the mixture for 30 min. 3.3 g of potassium bromide was dissolved in 5 ml of water to prepare a potassium bromide solution, which was added dropwise to the above mixed solution to form a white precipitate. After stirring for another 30 min, the mixed solution was transferred to a 50 ml polytetrafluoroethylene-lined reactor and reacted at 160° C. for 3 h. The reactor was taken out and cooled to room temperature. The precipitate formed by centrifuging the product was washed three times with deionized water and ethanol respectively, and then dried at 70° C. for 6 h to obtain a white bismuth oxybromide product.
[0058] (3) The white bismuth oxybromide prepared above was placed in a muffle furnace and calcined at 550°C for 3 hours to obtain Bi 24 O 31 Br 10 A pale yellow solid was then added with 2.7 g of Bi 24 O 31 Br 10 The powder was added to 1L of deionized water, isopropanol and tetrahydrofuran with a PANI concentration of 0.15g / L and a graphene oxide concentration of 0.06g / L, and ultrasonically treated for 30min. The mixture was then stirred for 24h. The mixed suspension was filtered, the precipitate was washed with deionized water for 3 times, and dried at 60°C for 24h to obtain Bi 24 O 31 Br 10 , PANI and GO composite photocatalysts.
[0059] In the above step (1), the molar ratio of the aniline solution to the hexadecyltrimethylammonium bromide is 10:1;
[0060] In the above step (3), Bi 24 O31 Br 10 :PANI:GO mass ratio is 95:5:2.
[0061] 2. Hydrogen production test
[0062] Photocatalytic hydrogen production: 24 O 31 Br 10 , PANI and GO composite photocatalyst powders were dispersed in 120 mL of methanol aqueous solution, the methanol content in the methanol aqueous solution was 30 mL, the top of the reactor was sealed with a rubber ring, so that the entire reaction system was a closed circulation system (Perfect Light Company Solaredge 700), and continuously irradiated with a 300 W xenon lamp. During the reaction, the reaction temperature was maintained at 5°C, the stirring speed was maintained at 400 rpm, and samples were taken every 1 hour, and the hydrogen production was detected by gas chromatography TCD.
[0063] Example 3
[0064] This embodiment provides a Bi 24 O 31 Br 10 , PANI and GO composite photocatalyst, and its preparation method is as follows:
[0065] 1.Bi 24 O 31 Br 10 Preparation of PANI and GO composite photocatalyst
[0066] (1) Preparation of conductive polyaniline: 0.46g aniline and 0.18g hexadecyltrimethylammonium bromide were dissolved in 80ml deionized water, and then 10ml 0.5mol / L hydrochloric acid was added dropwise, and then 10ml 0.5mol / L ammonium persulfate solution was slowly added dropwise at a rate of 3 seconds / drop. The mixed solution was stirred on a magnetic stirrer, and the reaction temperature was kept at 0-5°C. After reacting for 24h, the polyaniline precipitate was obtained by suction filtration. The precipitate was washed three times with deionized water and acetone respectively, and vacuum dried at 70°C for 18h to obtain a conductive polyaniline sample. 0.08g polyaniline and 0.02g graphene oxide were dispersed in 1L mixed solution of deionized water, isopropanol and tetrahydrofuran and mixed evenly.
[0067] (2) Preparation of bismuth oxybromide: 0.556 g of mannitol was dissolved in 25 ml of deionized water and stirred at room temperature for 30 min. Then, 0.4 g of polyvinyl pyrrolidone and 0.486 g of bismuth nitrate were weighed and added to the above solution. A rotor was added to stir the mixture for 30 min. 3.3 g of potassium bromide was dissolved in 5 ml of water to prepare a potassium bromide solution, which was added dropwise to the above mixed solution to form a white precipitate. After stirring for another 30 min, the mixed solution was transferred to a 50 ml polytetrafluoroethylene-lined reactor and reacted at 160° C. for 3 h. The reactor was taken out and cooled to room temperature. The precipitate formed by centrifuging the product was washed three times with deionized water and ethanol respectively, and then dried at 70° C. for 6 h to obtain a white bismuth oxybromide product.
[0068] (3) The white bismuth oxybromide prepared above was placed in a muffle furnace and calcined at 550°C for 3 hours to obtain Bi 24 O 31 Br 10 A pale yellow solid was then added with 2.7 g of Bi 24 O 31 Br 10 The powder was added to 1L of deionized water, isopropanol and tetrahydrofuran with a PANI concentration of 0.09g / L and a graphene oxide concentration of 0.03g / L, and ultrasonically treated for 30min. The mixture was then stirred for 24h. The mixed suspension was filtered, the precipitate was washed with deionized water for 3 times, and dried at 60°C for 24h to obtain Bi 24 O 31 Br 10 , PANI and GO composite photocatalysts.
[0069] In the above step (1), the molar ratio of the aniline solution to the hexadecyltrimethylammonium bromide is 10:1;
[0070] In the above step (3), Bi 24 O 31 Br 10 :PANI:GO mass ratio is 97:3:1.
[0071] 2. Hydrogen production test
[0072] Photocatalytic hydrogen production: 24 O 31 Br 10, PANI and GO composite photocatalyst powders were dispersed in 120 mL of methanol aqueous solution, the methanol content in the methanol aqueous solution was 30 mL, the top of the reactor was sealed with a rubber ring, so that the entire reaction system was a closed circulation system (Perfect Light Company Solaredge 700), and continuously irradiated with a 300 W xenon lamp. During the reaction, the reaction temperature was maintained at 5°C, the stirring speed was maintained at 400 rpm, and samples were taken every 1 hour, and the hydrogen production was detected by gas chromatography TCD.
[0073] Figure 2 A comparison chart of the hydrogen production of Examples 1-3 is presented, from which it can be seen that the rate of hydrogen production increases with time.
Claims
1. Application of bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst in the production of hydrogen from methanol; It is characterized in that The bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst comprises the following components in parts by weight: 80-98 parts of bismuth-rich oxybromide, 1-10 parts of polyaniline, and 1-5 parts of graphene oxide; The step of preparing hydrogen includes: dispersing the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst in a closed reactor filled with methanol aqueous solution, continuously irradiating with a xenon lamp, and continuously stirring; The bismuth-rich oxybromide is Bi 24 O 31 Br 10 ; The bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst is prepared by a method comprising the following steps: adding the bismuth-rich oxybromide into a polyaniline and graphene oxide solution, ultrasonically treating the solution, stirring and filtering the solution, washing the precipitate and drying the solution to obtain the bismuth-rich oxybromide, polyaniline and graphene oxide composite photocatalyst.
2. The use according to claim 1, characterized in that: A 300 W xenon lamp was used for continuous irradiation. The temperature in the closed reactor was 5° C. and the stirring speed was maintained at 400 rpm.
3. The use according to claim 1, characterized in that: The ultrasonic treatment time is 20-50 minutes, the stirring time is 20-30 hours, and the precipitate is washed with deionized water for 3-5 times.
4. The use according to claim 1, characterized in that: The drying condition is 50-80° C. for 20-24 hours.
5. The use according to claim 1, characterized in that: The bismuth-rich oxybromide is produced by calcining bismuth oxybromide.
6. The use according to claim 1, characterized in that: The bismuth-rich oxybromide is prepared by a method comprising the following steps: (1) dissolving mannitol in deionized water, stirring, and then further adding polyvinyl pyrrolidone and bismuth nitrate to obtain a mixed solution, and then dropping a potassium bromide solution into the mixed solution after stirring, and then stirring the mixed solution for a period of time to react, and then cooling the mixed solution to room temperature, and washing and drying the precipitate obtained by centrifuging the mixed solution to obtain a bismuth oxybromide product; (2) calcining the bismuth oxybromide product to obtain bismuth-rich oxybromide.
7. The use according to claim 6, characterized in that In step (1), after the potassium bromide solution is added dropwise to the mixed solution and stirred for 20-30 min, the mixed solution is transferred to a reaction kettle with a polytetrafluoroethylene liner and reacted at 140-180° C. for 3-5 h.
8. The use according to claim 1, characterized in that: The polyaniline is prepared by a method comprising the following steps: Aniline and hexadecyltrimethylammonium bromide are dissolved in deionized water, and then hydrochloric acid is added dropwise, followed by ammonium persulfate. The mixture is stirred for reaction and filtered to obtain a precipitate. The precipitate is then washed and dried to obtain polyaniline.
9. The use according to claim 1, characterized in that: The polyaniline and graphene oxide solution is prepared by a method comprising the following steps: dispersing polyaniline and graphene oxide in a mixed solution of deionized water, isopropanol and tetrahydrofuran and mixing them uniformly to obtain the polyaniline and graphene oxide solution.
Citation Information
Patent Citations
Preparation method of GO (graphene oxide) / Sb-BiOBr composite photocatalyst
CN105879886A
Surface oxygen vacancy-modified bismuth oxybromide photocatalyst and preparation method thereof
CN108993550A